2018
DOI: 10.1108/ijchm-03-2017-0152
|View full text |Cite
|
Sign up to set email alerts
|

Managing group flow experiences in escape rooms

Abstract: Purpose This paper theoretically and empirically aims to explore customer group flow experiences with an urban adventure game called “escape rooms”. Design/methodology/approach A comprehensive model of group flow antecedents and consequences is proposed and empirically verified by means of survey research and SEM methodology. Findings The results indicate that key determinants of group flow experiences are the collective challenge/skills balance, and theming and storytelling. Group flow, in turn, significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 97 publications
2
19
0
1
Order By: Relevance
“…In the introduction, players are introduced to ER rules, the materials, the gaming tools, and less often, the learning goals. Tutors take on a supervising and game master role to aid in providing clear instructions before the game starts, a finding which is consistent with other studies [10,52,104]. During the gameplay, instructors take on roles related to monitoring, moderating, guiding, facilitating, providing hints, encouraging participants, and debriefing.…”
Section: Key Findings and Implicationssupporting
confidence: 76%
“…In the introduction, players are introduced to ER rules, the materials, the gaming tools, and less often, the learning goals. Tutors take on a supervising and game master role to aid in providing clear instructions before the game starts, a finding which is consistent with other studies [10,52,104]. During the gameplay, instructors take on roles related to monitoring, moderating, guiding, facilitating, providing hints, encouraging participants, and debriefing.…”
Section: Key Findings and Implicationssupporting
confidence: 76%
“…These contributions both show the remarkable growth of the sector, its major relationships with recreation, and its special impact on the millennial generation. For their part (demandled approaches), Kolar (2017), Kolar and Čater (2018), Dilek andDilek (2018), andStasiak (2019) analyse users' experiences using etnography techniques. In these cases, the study area takes a second place and the phenomenon is contextualised within hospitality research as novelty experiences, post-modern tourism and the management of flows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As interactive entertainment in which individuals work with one another to find clues, solve puzzles, and complete particular tasks in order to "escape," these businesses offered the experiences that millennials craved. They wanted engaging and immersive consumption experiences that focus on shared experiences (Ashworth & Page, 2011;Brunner-Sperdin et al, 2012;Kolar & Čater, 2018;Taheri et al, 2017). Empirical studies confirmed that "shared fun is doubled fun" (Gajadhar et al, 2008).…”
Section: Figure 2 Classification Of Groupsmentioning
confidence: 99%